Pelatihan Pengolahan Air Bersih dengan Chlorine Diffuser sebagai Upaya Pengendalian Bakteri E. coli dan Total Coliform - Tri Wahyuni Kusuma Anggun; Viviana Kurnianingsih; Yuliana Intan Cayani; Ivana Azaria Widy; Hira Awali Nurmalinda; Akmal Fahreza Wibowo; Sugianto Sugianto; Narto Narto (FUNDAMENTUM : Jurnal Pengabdian Multidisiplin, 2026)
The microbiological quality of clean water in Dusun Kepuhan has not met regulatory standards, posing potential health risks to the community. Laboratory examination identified Escherichia coli at 21 CFU/100 mL and total coliform bacteria at 180 CFU/100 mL, exceeding the permissible limits established by the Indonesian Ministry of Health Regulation No. 2 of 2023. This community service program was conducted to enhance residents’ knowledge and practical skills in managing clean water through the application of a chlorine diffuser as a simple and practical disinfection method. The implementation process included problem identification, coordination with the local PAMSIMAS management, educational sessions, and hands-on demonstrations of diffuser preparation and use. Program effectiveness was evaluated using pre-test and post-test assessments involving 30 participants. The findings indicated a statistically significant improvement in participants knowledge following the training. The chlorine diffuser approach was considered appropriate for the community setting due to its ease of use, affordability, and gradual chlorine release mechanism. Continuous monitoring and sustained community commitment are necessary to ensure long-term implementation of safe water disinfection practices.